(untitled) (University of Khartoum Engineering Journal, 2022)
Chemical recycling process of polyethylene terephthalate (PET) into bis-hydroxyethyl terephthalatemonomer (BHET) was investigated for that its bottle grade consumption is reaching high levels specially inbottled water and soft drinks. Although the most commonly used recycling processes are in-plant and mechanicalmethods, it was found that the benefits and opportunities offered by chemical recycling makes it one of the mostinteresting processes to develop. Glycolysis of recycled polyethylene terephthalate (PET) from consumed bottledwater and soft- drink bottles was carried out with ethylene glycol (EG) for different weight ratios of PET to EGusing zinc acetate as catalyst at the boiling point of EG under nitrogenous atmosphere for a constant time of 3.5 h.PET:EG ratio was studied to get information on the reaction behavior and yield results taking into account thesolvent excess influence. Monomer and oligomers were characterized using FTIR technique. The possibility ofimproving the extraction process and the use of EG recovered from previous glycolysis reactions via distillation,membranes or other separation method could lead to an ameliorated economic and environmental process.